Smart energy monitoring system and optimization of energy consumption - Sarkar, Arnab; Ahmed, Baizid; Tuhin, Md. Momenul Islam; Rahman, Mahfuzur (Brac University, 2023)
This design report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.